Prognostic cut-off values of neutrofil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) for COVID-19: a case-control retrospective single-center study - Amalia Papanikolopoulou; Eftychia Eirini Maria Gourdoupari; Charalampos Charalampous; Polyxeni Alexiou; Vasiliki Rapti; Maria Effrosyni Livanou; Maria Kopelia; Vissaria Sakka; Konstantinos N Syrigos; Garyfallia Poulakou (Journal of Global Antimicrobial Resistance)
AIM: To identify prognostic cut-off values of the hematological indicators NLR and PLR for intubation and death in hospitalized patients with COVID-19. BACKGROUND: SARS-CoV-2 infection is characterized by lymphocyte and platelet reduction which inversely correlates with disease severity. METHODS: We retrospectively analyzed patients with COVID-19 pneumonia, sequentially admitted to our Infectious Diseases Department from June 2021 to December 2022 after the implementation of massive SARS-CoV-2 vaccination programs. Two cohorts were compared, with or without immunosuppression, using a propensity score-matching in 1:2 ratio. RESULTS: In total 393 from 400 collected patients (n=131, 33.3% immunocompromised with hematological malignancy or autoimmune condition and n=262, 66.7% non-immunocompromised) were enrolled: female: n=194 (49.4%); mean age 64.7 (SD=16.1). According to WHO criteria 54% (n=211) had severe COVID-19 and 53.9% (n=209) were fully/partially vaccinated against COVID-19. Patients with NLR on day 1 >5.06 and day 4 >6.40 had 5.27 and 9.79 times respectively, greater probability for intubation. Patients with PLR on day 1 >262.2 and day 4 >217.3 had 4.80 and 4.06 times respectively, greater probability for intubation (Table 1, Figure 1a). Patients with NLR on day 1 >4.82 and day 4 >6.41 had 5.84 and 11.35 times respectively, greater probability for death. Patients with PLR on day 1 >229 day 4 >205.4 had 4.73 and 4.49 times respectively, greater probability for death (Table 2, Figure 2). CONCLUSIONS: During the 3rd and 4th pandemic wave, cut-off values of the hematological indicators NLR and PLR display strong prognostic potential regarding intubation and death in hospitalized patients with COVID-19.